KARAKTERISTIK EDIBLE FILM PATI TAPIOKA DENGAN PENAMBAHAN MINYAK ATSIRI DAUN JERUK PURUT SEBAGAI ANTIBAKTERI - AGUNG SURYADI PRATAMA PUTRA; AKHYAR ALI; RASWEN EFENDI (Universitas Riau, 2017)
Edible film is a biodegradable packaging that composed from organic compound. Edible film can becontaminated by pathogen bacteria. Kaffir lime leaves essential oil has able to inhibit bacteria growth. Theaim of the study was to determine the best concentration of kaffir lime leaves essential oil as antibacteria ontapioca edible film. The experiment research used a completely randomized design, which consist of fivetreatments within three replications. The treatmens were concentration of essential oil i.e A1 (0% v/v), A2(0,5% v/v), A3 (1% v/v), A4 (1,5% v/v) and A5 (2% v/v). Data were obtained using analysis of variance andcontinued by Duncan New Multiple Range Test at level 5%. The result showed that the treatments significantlyaffected on water content, solubility, resistance of water, and water vapour transmission rate. Edible film withadditional of essential oil inhibit the growth of Staphylococcus aureus FNCC-19 and Escherichia coliFNCC-15. The best treatment was A5 (2% of essential oil) with thickness 0,156 mm, water content 22,87%,solubility 30,82%, resistance of water 161,29%, water vapour transmission rate 0,291 g/m2/h, diameterinhibition 20.16 mm of Staphylococcus aureus FNCC-19, and 30.45 mm of Escherichia coli FNCC-15.